Magnetization Transfer MR Imaging in Patients with Posttraumatic Epilepsy - Kumar, Rajesh; Gupta, Rakesh K.; Husain, Mazhar; Vatsal, Davender K.; Chawla, Sanjeev; Rathore, Ram Kishore S.; Pradhan, Sunil (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Intractable epilepsy is a well-recognized complication following head trauma, and many factors have been implicated in its pathogenesis. This study was performed to determine the severity of tissue damage after severe head injury as assessed with magnetization transfer (MT) MR imaging and the relationship of this damage with seizure intractability.METHODS: Forty-four patients, 13 without seizures (disease controls) and 31 with seizures, underwent T1-weighted MT MR imaging 1–10 years after head trauma. Phase-corrected gradient-echo (GRE) imaging was also performed in all patients to look for the presence of hemosiderin. All patients were evaluated for the presence of an MT abnormality beyond an abnormality seen on T2-weighted images, an MT abnormality within a T2 abnormality, and hemosiderin deposition.RESULTS: Patients with an MT abnormality beyond a T2 abnormality had a significantly higher intractability of seizures compared with those with an MT abnormality within a T2 abnormality (P < .05). In addition, the mere presence of hemosiderin deposit was not associated with seizure intractability; however, gliosis around the hemosiderin as seen on T1-weighted MT images was associated with seizure intractability.CONCLUSIONS: T1-weighted MT imaging may be of value in predicting the intractability of the seizure in delayed posttraumatic epilepsy.